Effect of alpha1-blockers on stentless ureteroscopic lithotripsy - Jianguo Zhu; Yuxiang Liang; Weihong Chen; Shuxiong Xu; Yuanlin Wang; Jianxing Hu; Hui-chan He; Wei-de Zhong; Zhaolin Sun (International Brazilian Journal of Urology, 2016)
ABSTRACT Objective To evaluate the clinical efficiency of alpha1-adrenergic antagonists on stentless ureteroscopic lithotripsy treating uncomplicated lower ureteral stones. Materials and Methods From January 2007 to January 2013, 84 patients who have uncomplicated lower ureteral stones treated by ureteroscopic intracorporeal lithotripsy with the holmium laser were analyzed. The patients were divided into two groups, group A (44 patients received indwelled double-J stents) and group B (40 patients were treated by alpha1-adrenergic antagonists without stents). All cases of group B were treated with alpha1 blocker for 1 week. Results The mean operative time of group A was significantly longer than group B. The incidences of hematuria, flank/abdominal pain, frequency/urgency after surgery were statistically different between both groups. The stone-free rate of each group was 100%. Conclusions The effect of alpha1-adrenergic antagonists is more significant than indwelling stent after ureteroscopic lithotripsy in treating uncomplicated lower ureteral stones.